Personal social responsibility in ecological citizenship: Dimensionality and scale measurement with Aiken Index Analysis - Istiqomah, Annisa; Murdiono, Mukhamad; Hajaroh, Mami (Universitas Negeri Yogyakarta, 2024)
Personal social responsibility emphasises the importance of positively benefiting society, including the environment. Responsibility is one of the values influencing ecological citizenship so that individuals can prioritise environmental issues and realise the importance of sustainable living. This research aims to develop an instrument for personal social responsibility in ecological citizenship as a measurement scale. The instrument's contents are validated by experts (expert judgment), and the test is then performed using the Aiken-V formula. The research results show that: 1) The dimensions of personal social responsibility in ecological citizenship are determined by indicators, namely a) Have an interest in considering environmental issues and resolving environmental issues; b) Have an interest in sustainable behavior in protecting and preserving the environment; c) Have awareness in considering and resolving environmental issues; d) Have awareness of sustainable behavior in protecting and preserving the environment; e) Actively participate in considering environmental issues and resolving environmental issues; f) Actively participate in sustainable behavior in protecting and preserving the environment; g) Take collective action in considering environmental issues and resolving environmental issues; h) Take sustainable collective action in protecting and preserving the environment; 2) The results of content validation using the Aiken V coefficient show that the 60 items have a very high level of validity, because they meet the criterion index of 0.80 < V â‰¤ 1.00. Further research should be able to examine public policy and develop environmental education and awareness.